Enhancing Reading Word Abilities in Slow Learner Students Through Global Contextual Method - Alamsyah, Alamsyah; Purwanta, Edi (Papanda Publisher, 2025)
Reading word difficulties significantly impact academic achievement among slow learner students, necessitating innovative pedagogical approaches that address their specific learning needs. This study investigated the effectiveness of the Global Contextual Method in improving reading word abilities among slow learner students in middle school settings. A Classroom Action Research design was employed over four months, involving three seventh-grade slow learner students at SMP Muara Bengkal, Indonesia. The intervention utilized a cyclical approach presenting complete words within meaningful contexts related to students' daily experiences, including school environment, family, and food-related vocabulary. Data collection involved pre- and post-intervention assessments, systematic classroom observations, and comprehensive skill evaluations across two implementation cycles. Baseline assessments revealed critically low reading abilities, with participants unable to read basic words independently and letter recognition ranging from 23% to 46%. Following the Global Contextual Method implementation, remarkable improvements were achieved across all participants. Average reading scores increased from 6.7% at baseline to 74.2% post-intervention, with individual improvements ranging from 55.5 to 74 points. Muhammad Rifici Saipik achieved the highest score (94%), while Human Sanuri demonstrated the greatest percentage improvement (91%). The contextual approach significantly enhanced student motivation, engagement, and long-term retention compared to conventional methods. These findings provide empirical support for constructivist learning principles in special education, demonstrating that meaningful, contextually relevant instruction can substantially improve reading outcomes for slow learners. The study contributes a practical pedagogical framework for inclusive education and highlights the importance of individualized, context-based approaches in addressing diverse learning needs.